SCHOOL MANAGEMENT IN THE IMPLEMENTATION OF THE NATIONAL ASSESSMENT PROGRAM AT DARUL ABRAR PRIVATE SMP SCHOOL - Nurma Elysa (JOURNAL OF HUMANITIES AND SOCIAL STUDIES, 2024)
To realize the mandate in Law no. 20 of 2003 concerning the National Education System, the government always carries out reforms that are adapted to the needs of the times. Before the National Assessment, the student evaluation system from a cognitive perspective was known as the National Examination. The implementation of the national exam using the UNKP system is considered to have several technical shortcomings, namely "the exam participants' answer papers are not allowed to get wet, folded, torn so that the answers to the exam questions that are rumored to be spread out cause students as exam participants to become unfocused and often reduce student motivation. To overcome this problem, the Government has begun implementing a computer-based education evaluation system or Computer Based Test (CBT). In its implementation, the computer-based examination system was continuously developed into a National Assessment which was officially announced on December 10 2019. The problem formulation in this research is (1) School management in implementing the National Assessment Program at Darul Abrar Private Middle School? (2) How does School Management Evaluate the National Assessment Program at Darul Abrar Private Middle School?. This research uses a qualitative approach and a case study type of research. Data collection techniques through interviews, observation and documentation. The researcher's efforts to analyze data were carried out using interactive techniques from data collection to completion of continuous data collection. The effort to check the validity of the data that the researcher used was the triangulation technique. The results of this research show that: (1) Management planning for the implementation of the National Assessment at Darul Abrar Private Middle School was carried out referring to several aspects, namely goals, targets and implementation steps. Meanwhile, to facilitate the implementation of National Assessment management, it follows several stages, namely: starting from the formulation and planning meeting, then implementation which is divided into strategies for students and strategies for the committee. (2) Darul Abrar Private Middle School, in terms of evaluation, strives to ensure that its students can continue to increase literacy. And perhaps implementing holistic learning by utilizing and developing all student potential in a balanced manner could be an alternative choice for educational institutions to cover the required literacy and numeracy.